Characterization of cross-linked enzyme aggregates (CLEA)-amylase from Zophobas morio - Easa, Muhammad Noor; Yusof, Faridah; Abd Halim, Amanatuzzakiah (Faculty of Food Science & Technology, Universiti Putra Malaysia, 2017)
Cross-Linked Enzyme Aggregates (CLEA) is known as one of the best enzyme immobilization technique nowadays. In this study, amylase extract from Zophobas morio (super mealworm) larvae was immobilized using acetone as the precipitant, glutaraldehyde as the cross-linker and bovine serum albumin as the additive. The characteristics of the produced CLEA were compared to the free soluble amylase, in terms of pH and temperature optimum and stabilities. The results displayed that CLEA and free amylase achieved an optimum temperature at 55°C and 45°C, respectively. CLEA-amylase also had showed greater stability against high temperature as compared to a free enzyme which had lost most of its activity when the temperature was set beyond 45°C. In comparison, at 65°C, CLEA-amylase still retained 73.2% of its activity. Results also revealed that CLEA-amylase has a pH optimum at 11, while it is pH 7 for free enzyme. Similarly, CLEA-amylase was more stable than the free form, over a wider range of pH, particularly at higher pH of 9, 10 and 11. Recyclability study showed that CLEA-amylase could retain 14.9% of its residual activity after 6 times of repeated uses. Since it is reusable, future works might include the evaluations of using CLEA-amylase at the industrial level, remarkably in detergent applications.